Out of the ordinary : finding hidden threats by analyzing unusual behavior - Hollywood, John S., 1973- (RAND Corp., 2004)
Presents a unique appraoch to selecting and assembling disparate pieces of information to produce a general understanding of a threat. The Atypical Signal Analysis and Processing schema identifies atypical behavior potentially related to terror actvity; puts it into context; generates and tests hypotheses; and focuses analysts' attention on the most significant findings. A supporting conceptual architecture and specific techniques for identifying and analyzing out-of-the-ordinary information are also described.
"MG-126-RC."
Title from title screen (viewed 11/23/2004).
Keywords: Criminal behavior, Prediction of -- United States.; Crime forecasting -- United States.; Criminal methods -- United States.; Terrorism -- Forecasting.; Terrorism -- Psychological aspects.; Intelligence service -- United States.; National security -- United States.; Criminalité -- Prévision -- États-Unis.; Modus operandi (Criminologie) -- États-Unis.; Terrorisme -- Prévision.; Terrorisme -- Aspect psychologique.; POLITICAL SCIENCE -- Political Freedom & Security -- Law Enforcement.; POLITICAL SCIENCE -- Security (National & International); Crime forecasting; Criminal behavior, Prediction of; Criminal methods; Intelligence service; National security; Terrorism -- Forecasting; Terrorism -- Psychological aspects; United States